Practical induction heat treating - Haimbaugh, Richard E. (ASM International, 2015)
This book is a quick reference source for induction heaters. It ties-in the metallurgy, theory, and practice of induction heat treating from a hands-on explanation of what floor people need to know. It includes practical tables and process analysis of induction heating, and was written to provide a combination of technical and practical information. For example, the book contains a method of analysis for various types of production processes on the same part; shows the recommended microstructure needed for induction hardening for various materials ranging from carbon to powdered metal steels; and discusses various nonconforming conditions in induction hardened parts and how to remedy these conditions. In the Second Edition, new material has been added including updated information on quenching methods, applications, inspection for quality control, and updated material on power supplies. --